Talent Management and Its Impact on The Organization's Leadership Performance: An Analytical Study of The Opinions of a Sample of Employees at the University of Baghdad - Kareem Jaber Dhahi (International Journal of Economics, Commerce, and Management, 2025)
This study aimed at the effectiveness of talent management in entrepreneurial performance at the University of Baghdad, where the study was conducted on the creativity of leaders in a number of colleges of the University of Baghdad in various (deans, heads of departments and assistant deans) where the questionnaire was used as a main tool in collecting successful data about the art of study, where ((204 questionnaires were distributed and (4 questionnaires were not returned, and (7) questionnaires were not valid for analysis, so the total number of cosmetic questionnaires for analysis is ((193 and the analysis and testing of hypotheses were conducted using the program (SPSSV.20), (PLS SMART), but the beginning that begins with the message was the descriptive analytical composition, and a group of colleges were selected at the University of Baghdad represented by linking (College of Law, College of Administration and Economics, College of Education Ibn Rushd, College of Engineering, College of Medicine, College of Arts, College of Sciences, College of Sciences Agricultural Specialties, College of Dentistry, College of Education and Nursing Sciences, College of Fine Arts, College of Education for Girls, College of Languages, College of Political Science, College of Medicine Al-Kindi, College of Medicine Al-Kindi, College of Media, College of Science for Girls).